Simulation of an hybrid blood cells micro-separator - Aissa, Foughalia; Abdul Rahim, Rosminazuin; Nordin, Anis Nurashikin; Ibrahim, Siti Noorjannah (IEEE, 2015)
The paper presents numerical analysis in threedimensional (3D) of a hybrid micro-separator that uses magnetophoresis (MAP) and hydrodynamic forces for blood cells separation. The separation between red blood cells (RBC) and white blood cells (WBC) is done by manipulating the differences of their physical and magnetic susceptibilities. The MAP force is induced from ferromagnetic line fabricated on a glass slide while the hydrodynamic force is obtained by a ‘U’ shape microfluidic channel. The analysis was conducted using finite element software, COMSOL Multiphysics®. The particles trajectories, which represent the actual blood cells’ movements on the microseparator, were profiled and show successful separation between RBCs and WBCs by using the MAP and hydrodynamic forces.This study also provides insights of challenges associated with blood separation towards the realization of better diagnostic devices.